EFFICACY OF IVABRADINE THERAPY ON RIGHT HEART PARAMETERS AND PROGNOSIS IN PATIENTS WITH SEVERE SYSTOLIC CHRONIC HEART FAILURE - K. G. Adamyan; L. R. Tumasyan; A. L. Chilingaryan (Евразийский Кардиологический Журнал)
The aim of study was to assess the efficacy of ivabradine (I, up to 15 mg) therapy on prognosis, right ventricular (RV) and atrial (RA) functional parameters, BNP, NT-pro-BNP and high sensitivity С reactive protein (CRP) levels in patients (pts) with III- IV NYHA FC systolic CHF. Methods. 76 pts with DCM (age 57.4) were randomly assigned to groups A (n=38, non receiving ivabradin, I) and group В (n=38, receiving I, 15 mg) in addition to ACEIs, diuretics, beta-blockers and digoxin. 1-, 2- and З-year mortality were 34.2, 39.5 and 50% in group A and 21.1, 28.9 and 39.5% in group B. Survival analysis revealed lower probability of 1-year, 2-year and З-year mortality (RR reduction at 38.3,26.8 and 21%) in pts, treated with I (p50%, hsCRP>40% and HR>40% and increase of RV EF and E/A at >25%, TAPSE>50% and RA functional index >60% after 1 year identified pts with cardiac events reduction. 2) Prognostic benefit, associated with I use, seems to be related to improvement of right heart parameters, neurohormonal and inflammation status and HR reduction.